2010
DOI: 10.5125/jkaoms.2010.36.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Study on bisphosphonate-related osteonecrosis of the jaw (BRONJ): case report and literature review

Abstract: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a side effect of Bisphosphonates (BPs) use. These days, oral bisphosphonates are normally prescribed to treat osteoporosis. Intravenous BPs are used extensively to treat osteolytic bone lesions related to multiplemyeloma and bone metastasis of solid cancers, breast cancer or prostate cancer. As the prescription of BPs is universalized and the number of people treated with BPs is increasing, an accurate understanding and proper management of BRONJ are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…They affect the formation of the ruffled border by osteoclasts and their adherence to bony surface resulting in decreased bone resorption activity. 7 Studies have shown higher incidence of BRONJ when bisphosphonates are administered intravenously than orally due to its decreased bioavailability on oral administration, 8 however our patient showed clinical manifestation of disease in shorter duration of oral administration due to corticosteroids which further increased its rate of progression. BRONJ is associated with the history of recent dental trauma; our patient gave no history of any such recent event.…”
Section: Discussionmentioning
confidence: 56%
“…They affect the formation of the ruffled border by osteoclasts and their adherence to bony surface resulting in decreased bone resorption activity. 7 Studies have shown higher incidence of BRONJ when bisphosphonates are administered intravenously than orally due to its decreased bioavailability on oral administration, 8 however our patient showed clinical manifestation of disease in shorter duration of oral administration due to corticosteroids which further increased its rate of progression. BRONJ is associated with the history of recent dental trauma; our patient gave no history of any such recent event.…”
Section: Discussionmentioning
confidence: 56%
“…In case of human, the bone remodeling rate of cortical bone of the jaw (alveolar process) was 10-20 times faster than that of iliac bone. [21] Naturally bone remodeling is a physiologically coordinated process involving bone formation by osteoblasts and bone resorption by osteoclasts. Imbalance between these two entities may lead to skeletal abnormalities characterized by increases or decreases in bone density.…”
Section: Etiopathogenesis Of Bps Induced Onjmentioning
confidence: 99%
“…That is why bones maintain a high remodelling status throughout life either in response to continuous mechanical stress or as a result of tooth movements or loss. In humans, the bone remodelling rate of cortical bone of the jaw (alveolar process) is 10-20 times faster than that of iliac bone [22]. Naturally, bone remodelling is a physiologically coordinated process involving bone formation by osteoblasts and bone resorption by osteoclasts.…”
Section: Aetiopathogenesis Of Bisphosphonate Related Osteonecrosis Ofmentioning
confidence: 99%
“…This can vary from subtle thickening of the lamina dura and alveolar crest to attenuated osteopetrosis like sclerosis. Other findings like osteolysis, soft tissue swelling, periosteal new bone formation, periapical lucencies, oroantral fistula and sequesters are likely to correspond with the presence of infection [22,43]. It is imagined that differential diagnosis includes chronic sclerosing osteomyelitis, osteoradionecrosis, bone metastasis and Paget's disease.…”
Section: Radiological Featuresmentioning
confidence: 99%